Emma au bal à la Vaubyessard - Jean-Marie Privat (Flaubert: Revue Critique et Génétique)
The story of the ball at the Vaubyessard is structured like a rite of passage. It presents the three constitutive stages (phase of separation, margin, reaggregation). But if in Flaubert's novel the heroine separates herself materially from her prosaic universe and if she runs wild very fleetingly in a symbolic margin, her initiation is cut short. Emma will remain on the threshold of this other glimpsed world. This liminality, far from condemning madame Bovary to insignificance, creates a specific narratological space and opens a poetic horizon to Emma's imagination.